2020
DOI: 10.1109/comst.2019.2949178
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Coping With Intentional Interference in Satellite Navigation for Manned and Unmanned Aircraft

Abstract: Intentional interference in satellite navigation is becoming an increasing threat for modern systems relying on Global Navigation Satellite Systems (GNSS). In particular, critical applications such as aviation can be severely affected by undetected and un-mitigated interference and therefore interference management solutions are crucial to be employed. Methods to cope with such intentional interference enclose interference detection, interference mitigation, interference classification, and interference locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 192 publications
1
52
0
1
Order By: Relevance
“…It shows the jamming detection results for test scenario OF-JAM.Z2D-Test 11, described in Section 5 using all the detectors described in Section 3 . All the considered detectors with the current recorded tests show that they work perfectly well under realistic scenarios and they confirm the previous findings of the authors based on simulations and lab-tests as reported in [ 1 , 19 , 37 ]. In particular, the estimated Probability of Detection ( ) is 100%, and the Probability of False Alarm ( ) is 0.…”
Section: On-field Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…It shows the jamming detection results for test scenario OF-JAM.Z2D-Test 11, described in Section 5 using all the detectors described in Section 3 . All the considered detectors with the current recorded tests show that they work perfectly well under realistic scenarios and they confirm the previous findings of the authors based on simulations and lab-tests as reported in [ 1 , 19 , 37 ]. In particular, the estimated Probability of Detection ( ) is 100%, and the Probability of False Alarm ( ) is 0.…”
Section: On-field Resultssupporting
confidence: 90%
“…Civil aviation and Air Traffic Control (ATC) are deeply tied to localization and navigation systems. Such systems are based on several technologies installed either on board or on the ground, including radio-beacons, RADAR, magnetic compasses, inertial navigation systems, and satellite positioning systems [ 1 ]. Global Navigation Satellite Systems (GNSSs) are complemented by their Wide-Area or Satellite-Based Augmentation Systems (WAAS, SBAS) to offer improved localization accuracy and an integrity framework to cope with flight-mode-dependent safety requirements [ 2 ].…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
See 3 more Smart Citations